Flexibility requirements and electricity system planning: Assessing inter-regional coordination with large penetrations of variable renewable supplies. (January 2020) - English, Jeffrey; Niet, Taco; Lyseng, Benjamin; Keller, Victor; Palmer-Wilson, Kevin; Robertson, Bryson; Wild, Peter; Rowe, Andrew
Abstract: Decarbonizing electricity generation through deployment of renewable technologies such as wind and solar is a key component of many climate change mitigation efforts. With increasing penetrations, the need to manage variability in renewable generation becomes critical. However, renewable variability is often poorly represented in energy planning studies which focus on energy and capacity adequacy. In this study, we used a hybrid capacity expansion and dispatch model with explicit inclusion of ramping and regulation services to examine balancing requirements in a decarbonizing electricity system. We find that ramping and regulation services needed for management of variable renewables alter the optimal mix of generation and transmission capacity relative to simpler planning models. In particular, we find enhanced value in expanding transmission capacity to access flexibility. Highlights: Representing short-term constraints in long-term energy models changes the outcome. Flexibility is a key constraint in systems with high penetrations of renewables. Interregional transmission can help provide system flexibility.